A meta-analysis of randomized trials assessing the effects of probiotic preparations on oral candidiasis in the elderly. (November 2017) - Ai, Ruixue; Wei, Jiao; Ma, Danhua; Jiang, Lu; Dan, Hongxia; Zhou, Yu; Ji, Ning; Zeng, Xin; Chen, Qianming
Highlights: Oral candidiasis incidence has escalated markedly, especially in the elderly. Use of probiotic agents to prevent candida-associated stomatitis is controversial. We performed a meta -analysis and systematic review of the literature. Probiotic agents can strongly prevent oral candidiasis in the elderly. Abstract: Objective: Oral candidiasis is the most common fungal infection and can be attributed in part to dysbiosis, an imbalance in the resident oral microflora. Therefore, probiotics, which counter pathogenic microorganisms through competitive, antagonistic, and immunological effects, have been used by some clinicians. To date, the effect of probiotics in preventing oral candidiasis in the elderly is controversial. A systematic review that summarizes and critically appraises the available clinical trials is therefore necessary. Design: Electronic searches were performed using the Pubmed, Embase, and Cochrane databases. Only randomized controlled trials were included. The Mantel–Haenszel test was used to appraise the odds ratio for single studies and an overall combined odds ratio for all studies combined. Results: Three studies matched the inclusion criteria and were homogeneous. The data from one study that estimated candida growth from plaque and saliva were subdivided, thus a total of four studies with 595 people were included. The overall combined odds ratio was 0.54 (95% CI: 0.38–0.77). Three studies provided that active treatment reduced the risk of oral candidiasis more than placebo: Hatakka et al. (OR 0.51, 95% CI 0.26 to 0.97; 192 participants, plaque); Kraft-Bodi et al. (OR 0.46, 95% CI 0.24 to 0.86; 174 participants, palatal); Kraft-Bodi et al. (OR 0.50, 95% CI 0.26 to 0.98; 174 participants, plaque), while one study provided reverse result: Ishikawa et al. (OR 1.24, 95% CI 0.48 to 3.58; 55 participants, saliva). Conclusion: Probiotics have a preventative effect on oral candidiasis in the elderly.